Development of a potentiometric sensor for the determination of saccharin in instant tea powders, diet soft drinks and strawberry dietetic jam - Santini, Alberto O. [UNESP]; Lemos, Sahra C. [UNESP]; Pezza, Helena Redigolo [UNESP]; Carloni-Filho, Joao [UNESP]; Pezza, Leonardo [UNESP] (Elsevier B.V., 2008)
The construction and the analytical evaluation of a potentiometric sensor, namely, Pt vertical bar Hg vertical bar Hg-2(Sac)2 vertical bar Graphite, where Sac stands for saccharinate ion, are described. This electrode has a wide linear dynamic range between 5.0 x 10(-7) and 1.0 X 10(-2) mol L-1 with a near-Nernstian slope of -58.1 +/- 1.1 mV decade(-1) and a detection limit of 3.9 x 10(-7) mol L-1. The potentiometric response is independent of the pH of the solution in the pH range 3.0-9.0. The electrode is easily constructed at a relatively low-cost with fast response time (within 10-30 s) and can be used for a period of 10 months without significant change in its performance characteristics. The proposed sensor displayed good selectivities over a variety of other anions (carboxylates and inorganic anions). The potentiometric sensor was successfully applied to the determination of saccharin in real food samples, that is, in instant tea powders, diet soft drinks and strawberry dietetic jam. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Saccharinate-sensitive electrode; Potentiometry; Instant tea powders; Diet soft drinks; Strawberry dietetic jam